Uno sguardo multidisciplinare sull’embodied experience nelle pratiche dello yoga - Svorova, Dana (Aesthetica Preprint, 2025)
Recently we witness a cultural debate centered on the concept of embodiment. Indeed, nowadays many fields of study, e. g. cognitive neurosciences, social psychology, PNEI, posturology, somaesthetics, agree that body and mind are a functional unit. This relatively new concept of embodiment manifests the full extension of the cognitive dimension to include the body, mind, emotions and environment in a dynamic process characterized by their reciprocal interaction. Similar view on a complexity of the human being we can find also in an ancient theoretical-experiential system of yoga. This paper highlights a possible link between modern scientific research and ancient oriental philosophy finding some interesting contact points based on so-called embodied experience. This last constitutes a substrate of well-being and personal growth confirming that yoga practice is an affective tool to oppose the negativity brought by everyday routine and its lasting marks on people’s health.